Pengaruh Model Pembelajaran Flipped Classroom terhadap Hasil Belajar Peserta Didik dalam Pembelajaran Fisika - Eva Putriani; Abdul Hamid; Evendi Evendi (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
The research entitled "The Effect of the Flipped Classroom Learning Model on Students' Learning Outcomes in Learning Physics" aims to determine the effect of the Flipped Classroom learning model on students' learning outcomes in physics learning on straight motion material at SMA Negeri 1 Teupah Tengah. This research methodology uses a quantitative approach with a Quasi Experimental Design research type with a None Quivalent design whose population in this study is all students of class X-MIA, totaling 2 classes. The sample in this study was taken using a total sampling technique, namely the number of samples equal to the total population of 40 students. The data collection techniques used were test techniques, questionnaires, and teacher observation sheets. The data analysis technique used a two-party t-test with the normality test and homogeneity test first as a prerequisite for the analysis. The results obtained are based on data analysis that has been carried out using a two-party t-test, namely the test value of tcount ≥ ttable that is 10,92 ≥ 1,68, so Ha is accepted, meaning that there is a significant effect of using the Flipped Classroom learning model on student learning outcomes in physics learning.